2014
DOI: 10.1128/jvi.01941-14
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Regulatory T Cells in Chronically Friend Retrovirus-Infected Mice Suppress Immunity to a Murine Cytomegalovirus Superinfection

Abstract: It is still unclear whether expanded and activated regulatory T cells (Tregs) in chronic viral infections can influence primary immune responses against superinfections with unrelated viruses. Expanded Tregs found in the spleens of chronically Friend virus (FV)-infected mice decreased murine cytomegalovirus (mCMV)-specific CD8؉ T cell responses during acute mCMV superinfection. This suppression of mCMV-specific T cell immunity was found only in organs with FV-induced Treg expansion. Surprisingly, acute mCMV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…Additionally, several studies using the lymphocytic choriomeningitis virus (LCMV) model have shown that NK cells, the development or reduction in the number of dendritic cells (DCs), and CD8 + T-cell-mediated immunopathology contribute to immunosuppression [2,[13][14][15]. This finding is in line with observations from studies of infections with other viruses showing that constant activation of CD8 + T cells in lymph nodes and spleen alters immune function [2,11]. It has been reported that LCMV infects B cells that produce neutralizing antibodies, which will be eliminated by immunopathological LCMV-specific CD8 + T cells [2].…”
Section: Introductionsupporting
confidence: 68%
“…Additionally, several studies using the lymphocytic choriomeningitis virus (LCMV) model have shown that NK cells, the development or reduction in the number of dendritic cells (DCs), and CD8 + T-cell-mediated immunopathology contribute to immunosuppression [2,[13][14][15]. This finding is in line with observations from studies of infections with other viruses showing that constant activation of CD8 + T cells in lymph nodes and spleen alters immune function [2,11]. It has been reported that LCMV infects B cells that produce neutralizing antibodies, which will be eliminated by immunopathological LCMV-specific CD8 + T cells [2].…”
Section: Introductionsupporting
confidence: 68%
“…Lindenberg and colleagues [ 23 ] showed that during acute mouse CMV infection Tregs suppress only T cell responses, whereas NK cell responses were not affected by Tregs. However, CMV infection of mice is not a very useful model to study the interaction of Tregs and NK cells because the virus does not efficiently activate or expand Tregs [ 40 ]. The effect of virus-induced Tregs on anti-viral NK cell responses can only be investigated in an infection model with strong Treg responses, like the FV mouse model [ 9 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we used a well‐established mouse model of MCMV brain infection to demonstrate a role for the PD‐1: PD‐L1 pathway in development of CD103 + CD69 + CD8 + bT RM populations in vivo following acute viral infection . Here, we followed‐up on those findings by first demonstrating that some of the bT RM were specific for a previously identified viral T‐cell epitope . We infected wild‐type (WT) C57BL/6 and PD‐L1 KO mice intracerebroventricularly with MCMV and evaluated expression of CD103 (marker for T RM ) on antigen‐specific CD8 + T‐cells at 30 days post‐infection (dpi).…”
Section: Resultsmentioning
confidence: 97%
“…In our previous study, we used a well-established mouse model of MCMV brain infection to demonstrate a role for the PD-1: PD-L1 pathway in development of CD103 þ CD69 þ CD8 þ bT RM populations in vivo following acute viral infection [10]. Here, we followed-up on those findings by first demonstrating that some of the bT RM were specific for a previously identified viral T-cell epitope [38].…”
Section: Antigen-specific Cd8 þ Cd103 þ T-cells Persisted Within the mentioning
confidence: 87%